Perennial Allergic Rhinitis and Absolute Eosinophil Count – A Descriptive Study - PRAKASH MANOHARAN; KEERTHIKA MATHIALAGAN; HARI PM (International Journal of Pharma and Bio Sciences, 2018)
The purpose of our study is to categorize Perennial Allergic Rhinitis patients based on Absolute Eosinophil count. The selected participants were given a questionnaire for basic information. Nasal smear and blood sample were collected and sent to Department of Pathology for histological examination. Number of eosinophil per high power field in nasal smear and absolute eosinophil count was done. Out of 98 patients, 40.2 % had AR for ≥ 20 years with a mean AEC of 2175,16.3 % had Eczema with a mean AEC of 2888, 38.7% had a positive family history of AR with a mean AEC of 3095. Based on the study, It can be concluded that patients who had longer duration of AR, associated eczema or a positive family history of AR had a significant increase in AEC value and were categorized to be on moderate grade based on Rothenberg classification. Comparatively, those patients who had shorter duration of AR, no eczema or a negative family history of AR fell on a milder grade. This delineation helps to modulate the treatment plan for patients presenting with Allergic Rhinitis based on their Absolute Eosinophil Count so as to avoid administering the patients with heavy anti-histamines and steroids without any benefit.